Long Pentraxin 3 as a Predictive Marker of Mortality in Severe Septic Patients Who Received Successful Early Goal-Directed Therapy - Kim, Sun Bean; Lee, Kyoung Hwa; Lee, Ji Un; Ann, Hea Won; Ahn, Jin Young; Jeon, Yong Duk; Kim, Jung Ho; Ku, Nam Su; Han, Sang Hoon; Choi, Jun Yong; Song, Young Goo; Kim, June Myung (Yonsei medical journal, 2017)
Pentraxin 3 (PTX3) has been suggested to be a prognostic marker of mortality in severe sepsis. Currently, there are limited data on biomarkers including PTX3 that can be used to predict mortality in severe sepsis patients who have undergone successful initial resuscitation through early goal-directed therapy (EGDT). A prospective cohort study was conducted among 83 severe sepsis patients with fulfillment of all EGDT components and the achievement of final goal. Plasma PTX3 levels were measured by sandwich ELISA on hospital day (HD) 0, 3, and 7. The data for procalcitonin, C-reactive protein and delta neutrophil index were collected by electric medical record. The primary outcome was 28-day all-cause mortality. 28-day all-cause mortality was 19.3% and the median (interquartile range) APHCH II score of total patients was 16 (13-19). The non-survivors (n=16) had significantly higher PTX3 level at HD 0 [201.4 (56.9-268.6) ng/mL vs. 36.5 (13.7-145.3) ng/mL, p=0.008]. PTX3 had largest AUC(ROC) value for the prediction of mortality among PTX3, procalcitonin, delta neutrophil index, CRP and APACHE II/SOFA sore at HD 0 [0.819, 95% confidence interval (CI) 0.677-0.961, p=0.008]. The most valid cut-off level of PTX3 at HD 0 was 140.28 ng/mL (sensitivity 66.7%, specificity 73.8%). The PTX3 and procalcitonin at HD 0 showed strong correlation (r=0.675, p<0.001). However, PTX3 at HD 0 was the only independent predictive marker in Cox's proportional hazards model (≥140 ng/mL; hazard rate 7.16, 95% CI 2.46-15.85, p=0.001). PTX3 at HD 0 could be a powerful predictive biomarker of 28-day all-cause mortality in severe septic patients who have undergone successful EGDT.